(untitled) (Revista Innova Educación, 2021)
The global health crisis caused by the Covid-19 pandemic has forced teaching and learning models to be rethought. The objective of this literature review was to demonstrate the teaching strategies and resources used in university teaching/learning in the biomedical area in the context of the Covid-19 pandemic. The literature search was in the PubMed, Science-Direct, and Scielo databases; original articles published in 2020 and 2021 were considered, which have addressed virtual simulation as a didactic strategy, its educational design, resources, implementation, and limitations. It is concluded that the different study programs in the biomedical area incorporated the virtual simulation of reality as a strategy and didactic resource in the face of the Covid-19 pandemic, obtaining satisfactory experiences.